PERANCANGAN SISTEM INFORMASI PENJUALAN PADA TOKO BUKU BINA MEDIA SARANA BERBASIS WEBSITE - Manurung, Sarjanisah; Simamora, Roni J.; Purba, Eviyanti Novita (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Bina Media Sarana bookstore needs to adopt information technology to enhance the efficiency and quality of its book sales services. In this context, the author designs a website-based sales information system to optimize the store's operations and expand its market reach. This study aims to design an effective and practical sales information system for the bookstore. Through needs analysis, intuitive user interface design, structured database development, and website-based system implementation, these objectives can be achieved. The sales information system enables customers to make online book purchases through the store's website. Additionally, it assists the store owner in inventory management, order processing, sales analysis, and shipment tracking. By implementing this system, it is expected that Bina Media Sarana Bookstore can improve operational efficiency, enhance the quality of customer service, and expand market reach through online presence. Furthermore, this system provides a competitive advantage for the store in the increasingly competitive book sales industry in this digital era.